2010
DOI: 10.1063/1.3486157
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanoparticle-doped biocompatible silk films as a path to implantable thermo-electrically wireless powering devices

Abstract: In this paper, we report on gold nanoparticle (GNP) doped silk films as an implantable and degradable heating element activated by light, which can be potentially used for wireless powering of implanted microdevices. Proof-of-concept experiments have been conducted by casting a GNP doped silk film on a miniature thermal-power chip, which generates ∼20 mW when illuminated by a green laser with an output power of 450 mW/mm2 at 532 nm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 35 publications
(29 reference statements)
1
28
0
Order By: Relevance
“…For example, gold nanoparticles were incorporated into silk fi lms to achieve an implantable and degradable heating element activated by light, which possesses potential for thermal therapy for in vivo medical applications, such as tumor removal or pain relief. [ 88 ] More recently, the fabrication of a fully dissolvable wireless heating device was reported, which consists of a serpentine resistor and a power-receiving coil, both made of Mg, on the silk substrate ( Figure 7 ). [ 36 ] The Mg heater was protected through being encapsulated in a silk "pocket", which can be used to program the lifetime of the device.…”
Section: Resorbable Substrates For Biodegradable Electronicsmentioning
confidence: 99%
“…For example, gold nanoparticles were incorporated into silk fi lms to achieve an implantable and degradable heating element activated by light, which possesses potential for thermal therapy for in vivo medical applications, such as tumor removal or pain relief. [ 88 ] More recently, the fabrication of a fully dissolvable wireless heating device was reported, which consists of a serpentine resistor and a power-receiving coil, both made of Mg, on the silk substrate ( Figure 7 ). [ 36 ] The Mg heater was protected through being encapsulated in a silk "pocket", which can be used to program the lifetime of the device.…”
Section: Resorbable Substrates For Biodegradable Electronicsmentioning
confidence: 99%
“…28 Doped silk protein films with gold nanoparticles can be activated by light, powering implanted devices. 93 As mentioned in a prior section, powering implantable devices, with batteries for example, will require replacement or maintenance.…”
Section: Thermal Conductive Bioelectronicsmentioning
confidence: 99%
“…Simple fabrication techniques such as single step transfers of metal micro patterns to silk films under ambient conditions is very appealing because it allows the simultaneous fabrication of microstructures over large areas of flexible silk films with high precision. Others have demonstrated that functionalized silk films doped with gold nanoparticles (Au-NP) that are light-activated heating elements which when interfaced with thermo-electronic components can wirelessly power micro devices [93]. Au-NP doped silk films were interfaced to thermoelectric chips by solution casting the polymer solution onto the active area of the chip.…”
Section: Regenerative Engineering and Limb Replacementmentioning
confidence: 99%